Fruits and vegetables dietary intake and its estimated consumption among adults receiving antiretroviral therapy in health facilities in Northcentral Ethiopia: a multi-facility cross-sectional study - Boneya, Dube Jara; Ahmed, Ahmed Ali; Yalew, Alemayehu Worku; Gebremedhin, Samson (Frontiers in Nutrition, 2024)
Background: Despite fruit and vegetable significant contribution to preventing a variety of chronic diseases and their potential to bolster immune responses and slow the progression of HIV infection to AIDS, there have been very few studies conducted among HIV-infected adults on fruit and vegetable (FAV) dietary intake in Africa, including Ethiopia. Hence, this study aimed to investigate the magnitude of FAV intake, and estimated consumption among HIV-infected adults receiving antiretroviral therapy (ART), in Northcentral Ethiopia.A multi-facility cross-sectional study was conducted on the FAVs intake among 865 HIV-infected adults receiving ART. A Poisson regression model with robust variance was fitted to identify associated factors with FAVs dietary intake.The study indicated that 655 (76.34%; 95% CI: 73.38, 79.07) HIV-infected adults reported consuming FAVs less than once per day, with 838 (97.67%, 95% CI: 96.41, 98.49) and 676 (78.79%, 95% CI: 75.92, 81.40) of HIV-infected adults reporting consuming fruits and vegetables less than once per day, respectively. The median (IQR) total FAV intake was 271.3 (IQR: 92.5, 439.5) g/day, with the median (IQR) intake of fruits and vegetables being 248.1 (IQR: 100.0, 400.0) g/day and 273.78 (IQR: 82.44, 348.33) g/day, respectively.We found that being divorced (APR=1.57, 95% CI: 1.16, 2.12), daily laborer (APR=2.08, 95% CI: 1.36, 3.20), employed (APR=1.77, 95% CI: 1.10, 2.84), and merchants (APR=1.59, 95% CI: 1.03, 2.47), as well as having children as caregivers (APR=1.61, 95% CI: 1.02, 2.55), an advanced WHO clinical stage (APR=1.32, 95% CI: 1.32(1.03, 1.69), and receiving ART for more than 8 years' duration (APR=1.78, 95% CI: 1.18, 2.67) were found to be independent predictors of FAV dietary intake among HIV-infected adults. From the findings, we understood that farmers were less likely to consume FAVs compared to employed individuals, daily laborers, and merchants. The finding indicated a very low level of FAV dietary intake among HIV-infected adults, receiving ART, falling below the minimum recommendation for adult physically active population. Despite living in a surplus area, farmers consume few fruits and vegetables. Early ART treatment, family therapy, and comprehensive nutritional counseling focusing on portion size and healthy diets, can improve FAV consumption and enhance children's caregiving roles.